Autoimmune hepatitis exerts a profound, negative effect on health‐related quality of life: A prospective, single‐centre study. (29th September 2018) - Janik, Maciej K.; Wunsch, Ewa; Raszeja‐Wyszomirska, Joanna; Moskwa, Maciej; Kruk, Beata; Krawczyk, Marcin; Milkiewicz, Piotr
Abstract: Background and Aims: Autoimmune hepatitis is a progressive chronic liver disease. Health‐related quality of life in autoimmune hepatitis has not attracted much attention so far. We prospectively assessed various aspects of health‐related quality of life in a well characterized group of patients with autoimmune hepatitis. Methods: In total, 140 patients with autoimmune hepatitis (mean age 40 ± 17 years) and 170 controls (mean age 36 ± 14 years) were included. Health‐related quality of life was evaluated with following questionnaires: The Short Form (36) Health Survey, Modified Fatigue Impact Score, State‐Trait Anxiety Inventory and Patient Health Questionnaire‐9 assessing depression. Results: Patients with autoimmune hepatitis showed a significant impairment of health‐related quality of life in all, but one, domains of The Short Form (36) Health Survey. Autoimmune hepatitis was associated with pronounced physical fatigue ( P < 0.001), anxiety ( P < 0.001) and depression ( P < 0.001). As compared to males, female patients demonstrated greater impairment of physical aspects of The Short Form (36) Health Survey and Modified Fatigue Impact Score. Twenty‐seven patients (19%) had moderate (Patient Health Questionnaire‐9 >10) and 14 (10%) moderately severe depression (Patient Health Questionnaire‐9 >15). Depression showed a very strong correlation with chronic fatigue ( R = 0.68; P < 0.001); physical and mental components of The Short Form (36) Health Survey ( R = 0.52/0.68 respectively; P < 0.001) and anxiety ( R = 0.47; P < 0.001). There was a trend towards better life's quality in patients treated with budesonide in some aspects of their health‐related quality of life. Duration of the disease, age at diagnosis, liver fibrosis and the presence of cirrhosis were not associated with health‐related quality of life. Conclusions: Health‐related quality of life is significantly impaired in patients with autoimmune hepatitis. Depression seems to be a dominant symptom affecting their well‐being, not associated with clinical and biochemical features of the disease.